2022
DOI: 10.2147/clep.s368826
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cigarette Smoking During Pregnancy and Genital Anomalies in Boys: A Register-Based Cohort and Sibling-Matched Design Study

Abstract: Purpose Cryptorchidism and hypospadias share several prenatal risk factors. However, in published studies, boys exposed to cigarette smoking during pregnancy have a higher risk of cryptorchidism and a lower risk of hypospadias. Using Danish register-based data, we revisited these findings with a cohort and sibling-matched design to investigate the potential effect of shared time-stable factors. Patients and Methods For the cohort study, we included 823,670 live-born, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Although our systematic review did not provide substantial evidence into an association between maternal exposure to cigarette smoking during pregnancy and testicular cancer, it remains uncertain whether our overall results are due to a lack of an association or perhaps due to the methodological limitations consistently observed across the included publications. Intriguingly, previous studies have found a link between maternal smoking during pregnancy and a higher risk of other parameters of male reproductive health, hereunder cryptorchidism [ 43 , 44 ], reduced sperm quality [ 45 , 46 , 47 ] and hypospadias [ 48 , 49 ], but also with contradictory results [ 44 , 50 , 51 ]. Nonetheless, cigarette smoke is known to contain several carcinogenic compounds [ 52 ] and components hereof, such as nicotine, have the ability to cross the placental barrier to the fetus [ 53 ].…”
Section: Discussionmentioning
confidence: 96%
“…Although our systematic review did not provide substantial evidence into an association between maternal exposure to cigarette smoking during pregnancy and testicular cancer, it remains uncertain whether our overall results are due to a lack of an association or perhaps due to the methodological limitations consistently observed across the included publications. Intriguingly, previous studies have found a link between maternal smoking during pregnancy and a higher risk of other parameters of male reproductive health, hereunder cryptorchidism [ 43 , 44 ], reduced sperm quality [ 45 , 46 , 47 ] and hypospadias [ 48 , 49 ], but also with contradictory results [ 44 , 50 , 51 ]. Nonetheless, cigarette smoke is known to contain several carcinogenic compounds [ 52 ] and components hereof, such as nicotine, have the ability to cross the placental barrier to the fetus [ 53 ].…”
Section: Discussionmentioning
confidence: 96%
“…42 studies, 9 studies, and 3 studies reported maternal active smoking, paternal smoking, and maternal passive smoking, respectively. 35 (79.5%) of the 44 papers included in this study employed a casecontrol design (1,9,10,13,14,20,22,27,30,, whereas 9 (20.5%) employed a cohort study design (25,32,34,(62)(63)(64)(65)(66)(67).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…35 We did not observe other potential risk factors, such as maternal smoking or paracetamol or other analgesics intake during pregnancy. [36][37][38] The role of maternal smoking is still debated, as some recent studies have actually shown a lower risk of hypospadias, 35,39 whereas others have reported a higher risk. 40 Concerning paracetamol intake during pregnancy, the results of previous studies are inconsistent, with some studies having found an association with hypospadias, 36 whereas others have not.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, paternal smoking was preferred to maternal smoking whose use as a risk factor for hypospadias has been challenged in the literature. 19,35,39,40 We then added maternal educational level into our multivariable model as a proxy for unmeasured socioeconomic levels to help control for a possible participation bias. Last, we decided not to adjust for preterm birth and the small-for-gestational-age (SGA) status because we suspected these characteristics to share common a cause with hypospadias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation